Hambatan Pasien Readmission dengan Gagal Jantung dalam Mempertahankan Kualitas Hidup Selama Masa Pandemik COVID-19 - Syahrul, Syahrul; Nafs, Ummul Tazkiyatun; Saipul, Sitti Zaimin Rahmat; Wahyudi, Adi Indra; Harisa, Akbar; Yodang, Yodang; Gaffar, Indra; Prianto, Andri; Armin, Cece Kirani; Wati, Irawan Patma (Faletehan Health Journal, 2023)
The surge in COVID-19 cases has a negative impact on the mental health of individuals, such as stress, depression, or fear, leading to a decline in immune response. The effects of this virus also affect the quality of life of heart failure patients. The aim of this research was to identify the barriers faced by heart failure patients in returning to hospital care during the COVID-19 pandemic and maintaining their quality of life. This study employed a quantitative method with a cross-sectional approach. The research samples consisted of 53 heart failure patients selected through accidental sampling with the inclusion criteria of patients readmitted to the hospital. The majority of patients experienced mild barriers, especially in self-care management. Non-compliance with treatments remained a major challenge for patients. The data regarding various barriers faced by heart failure patients in maintaining their quality of life during the COVID-19 pandemic can serve as a foundation for developing intervention models to enhance the quality of life for readmitted patients during the pandemic.